Predictive factors of acute respiratory events during initial induction chemotherapy in patients with advanced neuroblastoma. Issue 5 (13th July 2021) - Matsui, Motohiro; Makimoto, Atsushi; Nishio, Nobuhiro; Takahashi, Yoshiyuki; Urashima, Mitsuyoshi; Yuza, Yuki
Abstract: Background: Acute respiratory events (ARE) occasionally occur during induction chemotherapy as a complication in patients with advanced neuroblastoma. Aims: The present study aimed to identify the predictive factors of ARE, defined as severe hypoxia, during initial induction chemotherapy in patients with newly diagnosed advanced neuroblastoma. Methods and Results: The medical records of 75 consecutive patients in whom stage III or IV neuroblastoma was newly diagnosed between January 2003 and December 2018 at two medical institutions were retrospectively reviewed. The outcome was ARE, which were assessed by measuring oxygen saturation between days 1 and 14 of initial induction chemotherapy. Severe hypoxia was defined as grade 3 or higher according to the Common Terminology Criteria for Adverse Events version 4 (CTCAE v4.0) or decreased oxygen saturation at rest (e.g., pulse oximeter <88% or PaO2 ≤55 mmHg). Possible predictive factors on admission were first screened for using univariate analyses with P  = .05, then models of the predictive power of the outcome were evaluated by generating receiver operating characteristic (ROC) curves. Eleven patients (14.7%) had the outcome, including three (4.0%) who required respiratory support in the intensive care unit. The area under the curve of the ROC for the predictive factors screened by univariate analyses was 0.84 (95% confidence interval [CI]: 0.73–0.95) for lactate dehydrogenase (LDH) and 0.90 (95% CI: 0.82–0.98) for the disseminated intravascular coagulation (DIC) score. Conclusion: The LDH value and DIC score on admission may be clinically useful predictors of ARE during initial induction chemotherapy in patients with advanced neuroblastoma.